2021
DOI: 10.38212/2224-6614.3351
|View full text |Cite
|
Sign up to set email alerts
|

Pepsin-digested chicken-liver hydrolysate attenuates hepatosteatosis by relieving hepatic and peripheral insulin resistance in long-term high-fat dietary habit

Abstract: This study aims to clarify the effects of chicken liver hydrolysates (CLHs) on long-term high-fat diet (HFD)-induced insulin resistance (IR) and hepatosteatosis in mice. In vitro , the 400 μM oleic acid (OA)-added medium successfully stimulated the cellular steatosis on FL83B cells, and the cellular steatosis was attenuated ( p < 0.05) by supplementing with CLHs (4 mg/L). In vivo , the effects of CLHs on IR and hepatosteatosis development wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The blood glucose level per mouse was detected in 0, 30, 60, 90, and 120 min after the mice were orally administered with one g glucose/kg BW. The trapezoidal rule calculated blood glucose level under the curve ( AUC ) was calculated by the trapezoidal rule ( Wu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The blood glucose level per mouse was detected in 0, 30, 60, 90, and 120 min after the mice were orally administered with one g glucose/kg BW. The trapezoidal rule calculated blood glucose level under the curve ( AUC ) was calculated by the trapezoidal rule ( Wu et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Then, the brain homogenates were stored at −20°C for the Western blotting. The following procedure was done as described in Wu et al (2021) . The information of primary antibiotics used in this study was β-actin (sc-47778, 1:5000 dilutions, Level Biotechnology, Inc., New Taipei City, Taiwan), glucose transporter type 4 ( GLUT4 ) polyclonal antibody (#2213, 1:1000 dilution, Cell signaling Technology, Inc, Danvers, MA, USA), advanced glycation end-products (AGEs) polyclonal antibody (bs-1158R, 1:1,000 dilution, Bioss Inc. Woburn, MA), the receptor for AGEs (RAGE) polyclonal antibody (AB9714-l, 1:1,000 dilution, Merck KGaA, Darmstadt, Germany), c-Jun N-terminal kinase ( JNK ) polyclonal antibody (MA5-15183, 1:1,000 dilution, Thermo Fisher Scientific Inc.), and the cleaved Caspase 3 polyclonal antibody (#9664, 1:500 dilution, Cell signaling Technology, Inc. Danvers, MA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent research involves oral administration of hydrolyzed cartilage extract in the prevention of osteoarthritis ( Ma et al, 2021 ). Studies have also shown effects in the prevention of cardiovascular diseases ( Wu et al, 2020 ) and chronic liver diseases ( Chen et al, 2017 , Lin et al, 2017 , Wu et al, 2021 ), in antihypertensive treatments ( Bravo et al, 2019 , Mas-Capdevila et al, 2020 ), in the regulation of lipid metabolism as alternative treatments for obesity ( Yang et al, 2014 ) and to obtain antioxidant agents ( Chou et al, 2014 ).…”
Section: Biological Activities Of Peptides Obtained From Poultry By-p...mentioning
confidence: 99%
“…Although a further study for its mechanism is still needed, the anti-obesity effect was presented. The anti-obesity effects of poultry hydrolysates (i.e., egg chalaza, breast meat, and liver) were also reported, and the common mechanism was enhancing the lipolysis, fatty-acid βoxidation, and energy expenditure in mitochondria [ 81 83 ]. Overall, the formulation of multiple biohydrolysates or peptides may be another exploration for future scientists.…”
Section: Bioactive Ingredient Of Nutraceuticalsmentioning
confidence: 99%